Sertindole-induced hypomania: A case report - Atmaca, Murad; Kanmaz, Ebru (Cukurova Univ Tip Fakultesi Psikiyatri Anabilim Dali, 2008)
Although atypical antipsychotics are now commonly used in the treatment of bipolar disorder, they can also lead to manic and hypomanic states. Here, we report a case of hypomanic episode due to initiation of sertindole treatment in a male patient diagnosed with schizophrenia.
Keywords: Case; Hypomania; Sertindole